2016
DOI: 10.5038/2375-0901.19.3.4
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Bus Dwell Time and Time Lost Serving Stop in China

Abstract: The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 24 publications
0
11
0
1
Order By: Relevance
“…In our case we use the values a = 15 and b = 5 (seconds), which are consistent with those recommended in [5,31,33].…”
Section: Additional Problem Featuresmentioning
confidence: 88%
“…In our case we use the values a = 15 and b = 5 (seconds), which are consistent with those recommended in [5,31,33].…”
Section: Additional Problem Featuresmentioning
confidence: 88%
“…A bus stop influence area includes three sections: bus entry area, alighting and boarding areas for passengers, and exit area. In general, a stopped bus will slow from its running speed about 50 m before the bus stop, and accelerate back to its running speed about 30 m after the stop [44,45]. Thus, in this study, such a range of areas was regarded as the bus stop influence area, as shown in Figure 2a.…”
Section: Resultsmentioning
confidence: 99%
“…In our case we use the values a = 15 and b = 5 (seconds), which are consistent with those recommended in [2,12,16].…”
Section: Problem Definitionmentioning
confidence: 86%